Economic security of the enterprise through the lens of human capital development - Blyzkyi, A.; Belemets, I. (Економічний вісник Донбасу, 2025)
The article examines the role of economic security as a key factor in making managerial decisions and substantiates its importance as a stabilizing element that forms the adaptive capacity of the enterprise in the conditions of growing turbulence of the external environment. Dialectical reasoning, system analysis, as well as general scientific methods of analysis and synthesis were used, which ensured the complexity and multidimensionality of theoretical generalizations. The study highlights various and often contradictory interpretations of the concept of «economic security of the enterprise», which in the scientific discourse vary from a narrow resourcefinancial approach to integrated concepts focused on long-term stability and internal balance of the management system. Special attention is paid to the fact that economic security cannot be reduced only to countering crisis effects or ensuring the stability of financial flows. Based on logical argumentation, the article offers an updated perspective in which economic security is interpreted through the lens of human capital development, strategic motivation of personnel, and increasing the creative and innovative potential of employees. It is emphasized that it is precisely these intangible components that increasingly determine the ability of the enterprise to react qualitatively to threats, to form effective mechanisms of self-renewal and recovery, as well as to preserve competitive advantages in conditions of high dynamics of market processes. This approach allows for the formation of a broader conceptual vision of the factors that shape the economic security of enterprises, and emphasizes its role as a system integrator that combines the interests of development, stability, organizational flexibility and strategic coherence. The purpose of the article is to establish, trace, and summarize aspects of the formation of components of economic security of enterprises, to justify the role and importance of personnel for the economic security of an enterprise as the basis for making effective management decisions in crisis situations. The article proves that the formation of economic security of an enterprise is a multidimensional process that covers a set of interrelated components that reflect the financial, production, personnel, innovation, reputation, behavioral, information, and marketing aspects of the functioning of enterprises. The analysis shows that each of these components plays a significant role in ensuring the stability and ability of an enterprise to withstand both internal and external threats, thereby contributing to the overall level of economic security of the enterprise. The result of the study is a generalization of the identified aspects and proof that personnel are a system-forming element of the economic security of an enterprise. The role of human resources goes far beyond the traditional performance of operational tasks: employees shape the quality of management decisions, the adaptability of the organization, the effectiveness of internal communication, and the enterprise's ability to maintain structural integrity in crisis conditions. It has been confirmed that human capital is the basis for identifying and neutralizing threats, supporting not only reactive but also preventive mechanisms of economic security of the enterprise. The exceptional importance of personnel is determined by the fact that employees are the bearers of key competencies, knowledge, and management expertise necessary for effective decision-making in conditions of uncertainty and risk. The measurement of human resources forms the basis for innovation, communication, and strategic processes, determining the enterprise's ability to respond dynamically to changes in both the internal and external environment. The data obtained demonstrate that personnel are a critically important catalyst for the economic security of an enterprise and one of the main factors in making effective management decisions during crises. Therefore, the development and support of competent, motivated, and responsible personnel should become a strategic priority for enterprises seeking long-term stability and sustainable economic security. У статті розглядається роль економічної безпеки як ключового фактора прийняття управлінських рішень та обґрунтовується її значення як стабілізуючого елемента, що формує адаптивний потенціал підприємства в умовах зростаючої турбулентності зовнішнього середовища. Використовувалися діалектичні міркування, системний аналіз, а також загальнонаукові методи аналізу та синтезу, що забезпечило комплексність та багатовимірність теоретичних узагальнень. У дослідженні висвітлюються різні та часто суперечливі тлумачення поняття «економічна безпека підприємства», які в науковому дискурсі варіюються від вузького ресурсно-фінансового підходу до інтегрованих концепцій, орієнтованих на довгострокову стабільність та внутрішню збалансованість системи управління. Особлива увага приділяється тому, що економічну безпеку не можна зводити лише до протидії кризовим наслідкам або забезпечення стабільності фінансових потоків. На основі логічної аргументації у статті пропонується оновлена ​​перспектива, в якій економічна безпека тлумачиться крізь призму розвитку людського капіталу, стратегічної мотивації персоналу та підвищення творчого та інноваційного потенціалу працівників. Підкреслюється, що саме ці нематеріальні компоненти дедалі більше визначають здатність підприємства якісно реагувати на загрози, формувати ефективні механізми самооновлення та відновлення, а також зберігати конкурентні переваги в умовах високої динаміки ринкових процесів. Такий підхід дозволяє сформувати ширше концептуальне бачення факторів, що формують економічну безпеку підприємств, та підкреслює її роль як системного інтегратора, що поєднує інтереси розвитку, стабільності, організаційної гнучкості та стратегічної узгодженості. Метою статті є встановлення, простеження та узагальнення аспектів формування компонентів економічної безпеки підприємств, обґрунтування ролі та значення персоналу для економічної безпеки підприємства як основи для прийняття ефективних управлінських рішень у кризових ситуаціях. У статті доведено, що формування економічної безпеки підприємства – це багатовимірний процес, який охоплює сукупність взаємопов’язаних компонентів, що відображають фінансові, виробничі, кадрові, інноваційні, репутаційні, поведінкові, інформаційні та маркетингові аспекти функціонування підприємств. Аналіз показує, що кожен із цих компонентів відіграє значну роль у забезпеченні стабільності та здатності підприємства протистояти як внутрішнім, так і зовнішнім загрозам, тим самим сприяючи загальному рівню економічної безпеки підприємства. Результатом дослідження є узагальнення виявлених аспектів та доказ того, що персонал є системоутворюючим елементом економічної безпеки підприємства. Роль людських ресурсів виходить далеко за рамки традиційного виконання операційних завдань:Працівники формують якість управлінських рішень, адаптивність організації, ефективність внутрішньої комунікації та здатність підприємства підтримувати структурну цілісність у кризових умовах. Підтверджено, що людський капітал є основою для виявлення та нейтралізації загроз, підтримуючи не лише реактивні, а й превентивні механізми економічної безпеки підприємства. Виняткова важливість персоналу визначається тим, що працівники є носіями ключових компетенцій, знань та управлінської експертизи, необхідних для ефективного прийняття рішень в умовах невизначеності та ризику. Вимірювання людських ресурсів формує основу для інноваційних, комунікаційних та стратегічних процесів, визначаючи здатність підприємства динамічно реагувати на зміни як у внутрішньому, так і в зовнішньому середовищі. Отримані дані демонструють, що персонал є критично важливим каталізатором економічної безпеки підприємства та одним з основних факторів прийняття ефективних управлінських рішень під час криз. Тому розвиток та підтримка компетентного, мотивованого та відповідального персоналу повинні стати стратегічним пріоритетом для підприємств, які прагнуть довгострокової стабільності та сталої економічної безпеки.